Spirogyra oil-based biodiesel: response surface optimization of chemical and enzymatic transesterification and exhaust emission behavior - Sohail, Saqib; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Touqeer, Tooba; Anjum, Muhammad Kafeel; Rashid, Umer; Wan Ab. Karim Ghani, Wan Azlina; Choong, Thomas Shean Yaw (MDPI AG, 2020)
Algae are emerging as a major and reliable source of renewable biodiesel that could meet the energy requirements of the world. Like plants, algae produce and store oils in their cells. Algal samples were collected from Gujrat District, Pakistan, their oil content was analyzed, and the best oil producing alga was identified as Spirogyra crassa. After collecting sample, oil was extracted using the Soxhlet extraction method. Spirogyra oil was characterized physico-chemically for the evaluation of its quality. Acid value, density, saponification value, peroxide value, as well as viscosity and iodine values were determined and their values were 16.67 ± 3.53 mg KOH/g, 0.859 ± 0.050 g/cm3, 165.33 ± 13.20 mg KOH/g, 4.633 ± 0.252 meq/kg, 5.63 ± 0.833 mm2/mL, and 117.67 ± 13.01 mg I2/g, respectively. Chemical as well as enzymatic transesterification protocols were employed for biodiesel production using NaOCH3 and NOVOZYME-435, respectively. Different reactions parameters involved in transesterification were optimized by the response surface methodology. The optimized yield of biodiesel (77.3 ± 1.27%) by the chemical transesterification of algal oil (spirogyra) was observed by carrying out the reaction for 90 minutes at a reaction temperature of 45 °C using 1.13% catalyst (NaOCH3) concentration and 6:1 methanol:oil. Meanwhile, for enzymatic transesterification, the optimized yield (93.2 ± 1.27%) was obtained by conducting the reaction for 42.5 h at the temperature of 35 °C using 1% enzyme concentration and 4.5:1 methanol:oil. Fuel properties, including flash point, pour point, cloud point, fire point, kinematic viscosity, and density, were determined and their values are 125.67 ± 2.11 °C, −19.67 ± 0.8 °C, −13 ± 1 °C, 138.667 ± 2.52 °C, 5.87 ± 2.20 mm2/mL, and 0.85 6 ± 0.03 g/cm3, respectively. Fourier transfer infrared spectroscopic (FTIR) and Gas chromatography with flame ionization detector (GC-FID) analysis were performed for the monitoring of the transesterification process and fatty acid methyl acid (FAME) profiling, respectively.